Implementation of Mother Toddler Classes in Improving Growth and Development Stimulation Behavior of Mothers of 4-5 Year Old Toddlers in the Cimahi Tengah Health Center Working Area - Fathia Rizki; Meita Dhamayanti (Jurnal Ners, 2025)
The preschool period, particularly at the ages of 4–5 years, is a golden age that is crucial for a child’s growth and development. The active role of parents, especially mothers, is essential in supporting the stimulation of preschool children's development. A lack of stimulation can lead to developmental delays. One of the main contributing factors is the low level of maternal behavior regarding the importance of stimulation, which stems from the absence of a structured educational platform to assist mothers in fulfilling this role. Educational interventions such as mother-toddler classes have not been fully optimized to change maternal behavior. This study aims to determine the effect of mother-toddler classes on changes in maternal behavior in providing stimulation to preschool-aged children. The research design used is a pre-experimental approach with a one-group pretest-posttest design. The sample consisted of 39 mothers with children aged 4–5 years who met the inclusion and exclusion criteria. The study was conducted from October 2024 to April 2025. The intervention was carried out through mother-toddler classes over four weeks, divided into four sessions, and was evaluated using a validated and reliable questionnaire. The results showed that 64.1% of mothers had poor behavior in the pretest, while 61.5% had good behavior in the posttest. The McNemar test produced a p-value of 0.002 (p < 0.05). The conclusion of this study is that the implementation of mother-toddler classes is effective in improving the behavior of mothers in providing growth and development stimulation to children aged 4–5 years in the working area of Cimahi Tengah Public Health Center.